Determinants of Caesarean Deliveries in Bangladesh: A Multilevel Analysis of a Nationwide Population-Based Survey - Ireen, Shahjadi; Hasan, Md Zahid; Akter, Salma; Tareq, Muhammad; Begum, Mansura; Sultana, Rebeka; Parvin, Shahanaj; Soni, Most Sifat Muntaha (Jagannath University Journal of Science, 2024)
Caesarean section, a frequently conducted surgical procedure in obstetrics, is instrumental in safeguarding the well-being of both mothers and infants by addressing complications related to pregnancy and childbirth. While it significantly contributes to reducing maternal and infant mortality rates, its overuse can pose serious health risks. The prevalence of caesarean deliveries has surged globally, including in Bangladesh. This rise in caesarean deliveries has prompted this research to investigate the prevalence and various associated factors in the country. To achieve the study objectives, data were extracted from the Bangladesh Demographic and Health Survey (BDHS) conducted from 2017 to 2018. After preprocessing the data, a total of 4,884 women were included in the study. Frequency analysis was conducted to illustrate the distribution of sociodemographic characteristics among Bangladeshi women. Chi-square tests were performed to assess their association with caesarean delivery. Furthermore, multi-level logistic regression analysis was employed to identify the variables that have a significant impact on the likelihood of caesarean delivery. The study revealed that in Bangladesh, the prevalence of caesarean section deliveries was approximately 33.1%, with the majority of these occurring in the Dhaka division, accounting for approximately 25.3%. Women aged 20 or older were 1.62 times more likely to opt for a C-section during childbirth (OR 1.62, [1.38-1.89]) compared to those under 20. Overweight or obese women had twice the likelihood of delivering via C-section. Higher socioeconomic status also increased the probability of choosing a caesarean delivery. Women who had exposure to any form of media were 57% more likely to opt for a caesarean delivery (OR 1.57 [1.31-1.87]), while not working women had a 48% higher likelihood of having a C-section. Additionally, the study found that the use of caesarean delivery was positively associated with the husband's education level, the number of children previously born, and the number of antenatal care visits. The study revealed that the rate of C-sections in Bangladesh surpasses WHO recommendations significantly. It also identified various factors driving this trend, including women's education levels, socioeconomic status, media exposure, female obesity, age at first childbirth, and husband’s education. These insights may serve as a foundation for developing strategies to regulate the caesarean delivery rate. Urgent policy directives are essential within Bangladesh's healthcare system, coupled with vigilant monitoring of clinical indications for C-sections, to mitigate the adverse effects of unnecessary procedures. Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 31−44